1989
DOI: 10.2527/jas1989.6782181x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fertilization and Development of In Vitro Matured Bovine Follicular Oocytes

Abstract: Bovine follicular oocytes matured in vitro were fertilized in vitro using epididymal spermatozoa from five different bulls and then cultured to the blastocyst stage in vitro. The fertilization rate, based on one pair of pronuclei and presence of one sperm tail, ranged from 55.2 to 64.3%. Embryo development (cleavage to blastocyst stage) ranged from 21.4 to 31.0% of the cultured ova reaching 8 cells at 3 to 4 d after insemination to 1.3 to 3.7% reaching hatched blastocysts at 9 to 10 d. It is concluded that ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Leibfried-Rutledge et al (1989) reported that the length of the time that spermatozoa needed for capacitation, and hence for penetration of the oocytes, varied between bulls. Epididymal spermatozoa, on the other hand, did not show any 'bull-specific' variation when used in an IVF programme (Goto et al, 1989). It is possible that the responses of the spermatozoal membranes to the seminal plasma components, diluents, and freezing and thawing procedures vary between bulls, leading to differences in their behaviour during capacitation and acrosome reaction in vitro.…”
Section: Discussionmentioning
confidence: 90%
“…Leibfried-Rutledge et al (1989) reported that the length of the time that spermatozoa needed for capacitation, and hence for penetration of the oocytes, varied between bulls. Epididymal spermatozoa, on the other hand, did not show any 'bull-specific' variation when used in an IVF programme (Goto et al, 1989). It is possible that the responses of the spermatozoal membranes to the seminal plasma components, diluents, and freezing and thawing procedures vary between bulls, leading to differences in their behaviour during capacitation and acrosome reaction in vitro.…”
Section: Discussionmentioning
confidence: 90%
“…Frozen semen, prepared from epididymal spermatozoa (Goto et al, 1989) in 0.5-ml plastic straws, was thawed and washed 3 times with BO Medium (Brackett and Oliphant, 1975), without bovine serum albumin but supplemented with 5 mM caffeine, by centrifuga-…”
Section: Sperm and Sperm Head Preparationmentioning
confidence: 99%
“…While the microinjection technique can be superior to IVF in cases of male infertility or subfertility as pointed out by the authors, as a means of discriminating between different bulls, the IVF technique would be the method of choice based on their results. Goto et al (1989) used epididymal sperm to examine variation among bulls in rates of fertilization and development in vitro. In that study, a constant rate of fertilization and development in vitro was achieved, leading the authors to postulate that the seminal plasma may be the source of variation among different bulls as observed by other workers using ejaculated semen.…”
Section: Microinjectionmentioning
confidence: 99%